Towards a managed aquifer recharge strategy for Gujarat, India: an economist’s dialogue with hydro-geologists - Shah, Tushaar (Elsevier, 2014)
Gujarat state in Western India exemplifies all challenges of an agrarian economy founded on groundwater overexploitation sustained over decades by perverse energy subsidies. Major consequences are: secular decline in groundwater levels, deterioration of groundwater quality, rising energy cost of pumping, soaring carbon footprint of agriculture and growing financial burden of energy subsidies. In 2009, Government of Gujarat asked the present author, an economist, to chair a Taskforce of senior hydro-geologists and civil engineers to develop and recommend a Managed Aquifer Recharge (MAR) strategy for the state. This paper summarizes the recommended strategy and its underlying logic. It also describes the imperfect fusion of socio-economic and hydro-geologic perspectives that occurred in course of the working of the Taskforce and highlights the need for trans-disciplinary perspectives on groundwater governance.